PENGEMBANGAN PENANDA MIKROSATELIT PADA Pinus merkusii MENGGUNAKAN METODE DUAL SUPRESSION DAN SCREENING PENANDA - ILG Nurtjahjaningsih (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2010)
Aims of this study were to develop and characterize microsatellite markers from three species of Pinus i.e P. densiflora, P. Pinaster and P. Taeda were screened to amplify microsatellite in P. merkusii. The results showed that 5 out of the 12 developed microsatellite markers by dual suppression amplified at a single polymorphic locus; otherwise there was no polymorphic locus of the 12 screened microsatellite markers. However, it is difficult to compare the efficiency of these two method because of the limited number of the screened primers used in this study.